2023
DOI: 10.3389/fvets.2023.1136705
|View full text |Cite
|
Sign up to set email alerts
|

The effect of C–C motif chemokine ligand 2 supplementation on in vitro maturation of porcine cumulus-oocyte complexes and subsequent developmental competence after parthenogenetic activation

Abstract: Porcine embryos are used for a variety of applications. However, the maturation rate in vitro remains low, and novel in vitro maturation (IVM) techniques that facilitate the collection of mature oocytes are necessary. C-C motif chemokine ligand 2 (CCL2) is a key periovulatory chemokine present in cumulus-oocyte complexes (COCs). We aimed to examine the effects of CCL2 supplementation during IVM on oocyte maturation and embryonic development. The CCL2 concentration was significantly higher in porcine follicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In this research, Parthenogenetic embryos were employed. Because parthenogenesis technology is mature, the embryo development state is good, a lot of embryos with diploid features are easy to obtain, and there is no bias of paternal contribution; porcine parthenogenetic embryos were used as an excellent model to detect early embryo development [36,37]. We found that exposure to 100 µM BDE-47 significantly decreased the blastocyst rate.…”
Section: Discussionmentioning
confidence: 85%
“…In this research, Parthenogenetic embryos were employed. Because parthenogenesis technology is mature, the embryo development state is good, a lot of embryos with diploid features are easy to obtain, and there is no bias of paternal contribution; porcine parthenogenetic embryos were used as an excellent model to detect early embryo development [36,37]. We found that exposure to 100 µM BDE-47 significantly decreased the blastocyst rate.…”
Section: Discussionmentioning
confidence: 85%
“…Mature oocytes were gathered 42-44 h post IVM, and their internal levels of glutathione (GSH) and reactive oxygen species (ROS) were evaluated using a previously described method (30). Cell Tracker Blue 4-chloromethyl-6, 8-difluoro-7-hydroxycoumarin (CMF2HC) and the 2' , 7'dichlorodihydrofluorescein diacetate (H2DCFDA) (Invitrogen, Carlsbad, CA, USA) indicators were used to detect the GSH and ROS levels within the ooplasm, respectively.…”
Section: Evaluation Of Intracellular Gsh and Ros Levelsmentioning
confidence: 99%
“…After IVM, Metaphase II (MII) oocytes from each group were chosen and rinsed with a calcium-free TLH/PVA medium. The process of Parthenogenetic activation (PA) was carried out using a standard method (30). MII oocytes were rinsed twice in a 280 mM mannitol solution containing 0.01 mM CaCl 2 and 0.05 mM MgCl 2 .…”
Section: Parthenogenetic Activation Of Porcine Oocytesmentioning
confidence: 99%
See 2 more Smart Citations